Impact of comorbidities and ablation strategy on outcome after pulmonary vein isolation with cryo-balloon in patients with non- paroxysmal atrial fibrillation. (14th October 2021) - Berkowitsch, A; Hutter, J; Zaltsberg, S; Tomic, M; Kahle, P; Hain, A; Kuniss, M; Neumann, T
Abstract: Background: Presence of several comorbidities in patients with atrial fibrillation is well known, but impact of them on outcome after pulmonary vein isolation with cryo-balloon is not enough investigated. First aim of the study was analysis of the impact of comorbidities on long term outcome after PVI with cryo-balloon new generation (CBA) and secondary goal was evaluation of the impact of additional posterior roof ablation (PRA) in these patients. Methods: Patients with non-paroxysmal AF ablated with CBA in our institution since May 2012 and completed follow up >3 months were enrolled in the study. The history of AF, cardiac comorbidities (CAD, Non ischemic-cardiomyopathy, heart insufficiency, right ventricular dysfunction) diabetes mellitus, and renal failure were assessed at admission, all patients received echocardiographic examination and blood test. After a single trans-septal access and PV angiography PVI was performed using a 28-mm CBA. Mapping of PV signals before, during, and after each cryo application was performed with a 3F lasso catheter. The procedural endpoint after PVI was defined as complete elimination of all fragmented signals at the PV antrum with verification of entrance and exit block. In some patients PRA was performed additionally to PVI at discretion of physician. The primary endpoint of this study was the first documented recurrence of atrial tachyarrhythmia (>30 sec.), hospitalization due to cardio-vascular cause, re-do procedure or re-administration of anti-arrhythmic drugs. Results: Among 560 patients 78 (13.9%) had no comorbidity and 299 (53.4%) were lasted with >1 comorbidity. A total of 260 (46.4%) recurrences were obtained within median follow up of 28 (12–57) months. Female gender, long time from first diagnosis >12 months and cardiac comorbidity were revealed to be independent predictors for long term recurrences whereas additional PRA performed in 176 pts independently improved outcome (61.9% vs 49.7%). Conclusion: Cardiac comorbidities increased probability of post ablation recurrences, but performing of additional posterior roof ablation improved outcome in our cohort. These results should be confirmed in multi-center randomized study Funding Acknowledgement: Type of funding sources: None.